Achyranthes bidentata polypeptides promotes migration of Schwann cells via NOX4/DUOX2-dependent ROS production in rats. (23rd March 2019) - Song, Honghua; Zhao, Hualong; Yang, Lingyan; Li, Lilan; Zhang, Tuanjie; Pan, Jiacheng; Meng, Yali; Shen, Weixing; Yuan, Ying
Highlights: The first study showing the migration effect of ABPP on primary Schwann cells in a proper concentration range. Revealing the key role of NOX4 and DUOX2 in ABPP-induced ROS production and consequential SCs migration. Providing further theoretical reference for the clinical application of ABPP in the treatment of peripheral nerve injury. Abstract: Achyranthes bidentata polypeptides (ABPP), an active polypeptides isolated from the aqueous extract of Achyranthes bidentata Blume, contributes to the regeneration of injured peripheral nerves by promoting migration of Schwann cells (SCs). In this study, we aimed to investigate the possible mechanism underlying the ABPP-induced migration of primary cultured rat SCs. Transwell migration assays indicated that ABPP promoted SCs migration in a concentration-dependent manner by inducing production of NADPH-oxidase (NOX)-derived reactive oxygen species (ROS). Inhibition of ROS production by NOXs inhibitor apocynin (APO) or diphenyleneiodonium (DPI) partially blocked ABPP-mediated SCs migration. Furthermore, by using real-time polymerase chain reaction analysis and siRNA interference technique, we verified the participation of NOX subunit 4 (NOX4) and dual oxidase 2 (DUOX2) in ABPP-induced ROS production and consequential SCs migration. Taken together, these results demonstrated that ABPP promoted SCs migration via NOX4/DUOX2-activated ROS in SCs.